Modulation of selected hemolymph factors in the Indian edible oyster Crassostrea madrasensis (Preston) upon challenge by Vibrio alginolyticus - Giji, Ittoopp; George, K C; Rani Mary, George; Sobhana, K S; Sanil, N K (Indian Journal of Fisheries, 2016)
Juveniles of Crassostrea madrasensis (mean weight 85.5 Â± 2.3 g) were exposed to live cells of Vibrio alginolyticus (1.2 x 106 cells g-1) by intramuscular injection. Hemolymph samples were collected at different time intervals to study the modulations in the cellular and humoral factors. There was an increase in total hemocyte count, percentage granulocytes, serum protein, serum acid phosphatase, serum phenol oxidase and serum lysozyme in response to bacterial challenge upto three to five days post-injection. A decrease in the ability of hemocytes to phagocytose yeast cells was also noted. The hemolymph parameters of the test group became similar to that of control animals within two weeks of exposure to live bacterial cells.